Acceleration of Healing in Full-Thickness Wound by Chitosan-Binding bFGF and Antimicrobial Peptide Modification Chitosan Membrane - Hou, Lin; Wang, Wei; Wang, Mei-Kun; Song, Xue-Song (Frontiers in Bioengineering and Biotechnology, 2022)
Skin wound healing is an important clinical challenge, and the main treatment points are accelerating epidermal regeneration and preventing infection. Therefore, it is necessary to develop a wound dressing that can simultaneously cure bacterial infections and accelerate wound healing. Here, we report a multifunctional composite wound dressing loaded with chitosan (CS)-binding bFGF (CSBD-bFGF) and antimicrobial peptides (P5S9K). First, CS was used as the dressing matrix material, and P5S9K was encapsulated in CS. Then, CSBD-bFGF was designed by combining recombinant DNA technology and tyrosinase treatment and modified on the dressing material surface. The results show that the binding ability of CSBD-bFGF and CS was significantly improved compared with that of commercial bFGF, and CSBD-bFGF could be controllably released from the CS dressing. More importantly, the prepared dressing material showed excellent antibacterial activity in vivo and in vitro and could effectively inhibit the growth of E. coli and S. aureus. Using NIH3T3 cells as cellular models, the results showed that the CSBD-bFGF@CS/P5S9K composite dressing was a friendly material for cell growth. After cells were seeded on the composite dressing surface, VEGF and COL-I gene expression in cells was significantly upregulated. Finally, the full-thickness wound of the rat dorsal model was applied to analyse the tissue repair ability of the composite dressing. The results showed that the composite dressing containing CSBD-bFGF and P5S9K had the strongest ability to repair skin wounds. Therefore, the CSBD-bFGF@CS/P5S9K composite dressing has good antibacterial and accelerated wound healing abilities and has good application prospects in the treatment of skin wounds.